O COTIDIANO DA EQUIPE PROFISSIONAL DO CENTRO MUNICIPAL DE APOIO ESPECIALIZADO – CEMAE DE TELÊMACO BORBA – PR: A RELAÇÃO MULTIDISCIPLINAR E INTERDISCIPLINAR NA EDUCAÇÃO INCLUSIVA - Pedroso, Jucelene Mendes Valério (2015)
This research has as object of study "The daily work experienced by professionals in the Municipal Center for Specialized Support - CEMAE of Telêmaco Borba - PR, in the context of inclusive education policy, considering the relation between the multidisciplinarity and interdisciplinarity, its tensions and possibilities, bounded through the years 2005-2012. It has as the main objective to analyze how it was in the daily work the relationship between multidisciplinarity and interdisciplinarity, from CEMAE team experience in the context of inclusive education in the municipality of Telemaco Borba - PR. The research is based on a qualitative approach and developed using the following methodological instruments: literature, documentary research, individual interviews, and content analysis in the thematic-categorical format. The participants were team members of CEMAE (Social Worker, Psychologist, Educator, speech therapist), and the testimonials were collected from a semi-structured script with open and closed questions, characterized by eight questions that were about the work experience from each other. The process of investigation led it to raise six categories of analysis of empirical material, being: experience of the team; specificity of professional work on this team; challenges present in the experience of CEMAE professionals; tensions and dilemmas in overcoming multidisciplinary process for interdisciplinarity; social relevance of the team's experience in CEMAE; understanding of interdisciplinarity practice. Given the above, this paper was organized in four chapters: the first chapter entitled "State and public policies: education in the Brazilian context"; the second chapter called "Public Policy Brazilian Education and Special Education in the Perspective of Inclusive Education"; the third chapter "Daily work and interdisciplinarity: contextual elements for understanding the interdisciplinarity process"; Finally, the fourth chapter "The daily work of the interdisciplinarity team of Municipal Support Center Specializing in Telêmaco Borba - PR: experience in the years 2005-2012". Thus, it is concluded that the staff recognizes the interdisciplinarity work as a guideline focused on educational inclusion, while points to the need to overcome barriers in the daily work that generate fragmentation of their actions and their objectives.